New Historicism in Romanian Fiction - MURESAN, MARIA (Helsinki Romanian Studies Journal, 2024)
Our research is an inquiry into the validity of a theoretically constructed framework for the study of literature which emerged at the threshold between the eighth and ninth decades of the last century: New Historicism. This inquiry implies both a theoretical and an applied dimension, that is, an assessment of the epistemological tenability of new historicist premises, assumptions and line of argument completed by the successful application of this grid on texts, in the sense of securing an interpretation which sounds appropriate and edifying. The necessity of this approach seems to us to arise out of the paradoxical situation that, although the masterpieces of Romanian fiction published after the war are in the magic realist or metahistoriographic key, the Romanian critics who used the New Historicist grid in their interpretation are just a few, and not the most authoritative figures in shaping the canon. The new historicism is neither popularization nor schematization, it is the new breath that will allow us to keep a minimum relationship of the people we are with the ideas that were. Our paper brings up proofs in this argument, some of them originating in a theoretical discussion of the premises of New Historicism in the context of other critical schools, of the present exegesis of literary history, theory and criticism. Other arguments are provided by the epistemology of the age which carries the traces of the linguistic turn, that is, the reversal of the relationship between language and referent. History is no longer conceived of as the non-problematic and truthful record of past events; it has been deconstructed as an act of language, a narrative following no other rules than the generic ones. We were also pleased to draw attention to valuable Romanian contributions to the research and discourse on this subject.